The Role Of Nurses and The Quality of Health Services With The Satisfaction of BPJS Patients In Junrejo Puskesmas Batu City - Pamungkas, Restu; Indasah, Indasah; Koesnadi, Koesnadi (Master of Public Health Program Universitas STRADA Indonesia, 2019)
Patient satisfaction is related to service quality. By knowing the level of patient satisfaction, hospital management can improve service quality. Patient satisfaction is considered as one of the most important quality dimensions and is the key to success in health organizations that is also affected by the role of nurses. The purpose of this study was to determine the effect of nurse roles and service quality on BPJS patient satisfaction. The research design used was cross sectional with questionnaire sheet instruments. The population of this study were 230 BPJS patients. 144 samples used random sampling techniques, while to determine the effect between variables used ordinal regression test with a significant level of 0.05. Based on the results of the study it was found that the role of good nurses was 64 (44.4%) respondents and most of the good quality services were 88 (61.1%) and satisfaction in the satisfied category was 124 (86.1%). The results of the data analysis showed that there was an influence of the nurse's role factor on satisfaction. It was known that the Sig (2-tailed) value had 0.00 and the service quality factor had an effect on satisfaction, this was known as Sig (2-tailed) which had a number 0.049. The existence of a good role from nurses will improve service quality and will improve BPJS patient satisfaction.